Biological performance and biochemical interactions of mustard aphid (Lipaphis erysimi) in Brassica juncea - SAMAL, IPSITA; DHILLON, MUKESH K; SINGH, NAVEEN (The Indian Journal of Agricultural Sciences, 2021)
Present studies were carried out on development and survival of Lipaphis erysimi (Kaltenbach) on diverse Brassica juncea (L.) Czern. & Coss. genotypes, and decipher the role of certain biochemical compounds in plant defense against mustard aphid. There were significant differences among test B. juncea genotypes for total nymphal duration, reproductive period, total developmental period, fecundity and survival of L. erysimi. The development period was significantly longer on PDZM 31, NRCHB 101, RP 7-3-2-2-1, TS 18-5124, RP 11-2-1-3-1, YSG, RLC 3, NPJ 50, IC 355399, MSTWR 17-1, EC 61-9-2-2-2, GP 454 and Kranti, while fecundity and survival were significantly lower on RLC 3, Kranti, IC 355399, Rohini, GP 454, NPJ 50 and TS 18-5124 as compared to other B. juncea genotypes. The biochemical constituents like, total antioxidants, tannins, phenols and FRAP were also significantly higher in RLC 3, Kranti, IC 355399, Rohini, GP 454, NPJ 50 and TS 18-5124 as compared to other B. juncea genotypes, except in a few cases. The total antioxidants and total tannins had significant and negative association, and explained 78.5% and 91.3% variability for fecundity and survival of L. erysimi, indicating their detrimental effects on progeny production and survival of mustard aphid on B. juncea. Present studies suggest that the B. juncea genotypes RLC 3, IC 355399, Rohini, GP 454, NPJ 50, TS 18-5124 and Kranti have higher amounts of test defense biochemicals and impart adverse effects on the reproductive period, fecundity and survival of L. erysimi.